Metaphors inspiring design: a study on how designers make sense of patients' narratives of diabetes. Issue 1 (2nd January 2019) - Sen, Elif; Merzali Celikoglu, Ozge
Abstract: This paper aims to reveal the value of metaphorical content obtained from users as an inspiration source for designers. Studies related to metaphors within design research predominantly focus on how designers generate and utilize metaphors in design processes and it appears that the user's side has not yet been explored. Our research started by relying on the relevant findings of another domain, health sciences, where studies revealed the value of metaphor in easing communication, enhancing understanding of patients, and creating therapeutic effects. By transferring this knowledge, it is assumed that the metaphorical content provided from users can improve communication between users and designers and inspire designers during the ideation process. This hypothesis is examined in a two-staged study including diabetes patients and designers: an online survey about living with diabetes is conducted within an online diabetics' community and then individual designers are asked to interpret the outcomes of the survey to develop ideas that can improve the lives of diabetics. Through a qualitative content analysis, it is found that participant designers prefer to focus on user expressions with rich metaphorical contents and utilize these metaphorical contents to generate initial design concepts by providing deeper insights into users' understanding.